Lip Reconstruction Using Radial Forearm Freeflap After Radical Excision of Squamous Cell Carcinoma: A Case Report - Setiawan, Eko; Sari, Erythrina Permata (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2019)
INTRODUCTION: The main treatment modality for squamous cell carcinoma of the head and neck is by surgical wide excision. Post-excision reconstructive surgery is essential for restoring aesthetics and function. Fasciocutaneous free-flap is an acceptable method for reconstructing a wide lession of the face since the technique does not cause significant morbidity.CASE REPORT: A 41 year-old female was diagnosed with squamous cell carcinoma (T3N0M0) of the inferior lip after achieving tumor-free margin radical excision. Reconstruction of the defect was made with radial forearm freelap followed by a three-phase refinement flap. The patient was left with a aesthetically acceptable lip without other facial morbidity.DISCUSSION: Reconstructive surgery following a widely excised tumor of the lips requires special attention because of its important physical and aesthetical role. Radial forearm freeflap causes minimal facial morbidity since the technique does not require donor tissue from the face. Other benefits include adequate tissue thickness, minimal contracture and unaltering skin color. Further refinement flaps is needed to complete the reconstruction process.CONCLUSION:Â Radial forearm free flap is a good choice for reconstruction a wide lession following a wide excision of lip tumor.